The Effect of Peer Support, and Mindfulness on Subjective Well-Being Students in Yogyakarta Dormitory - Elisa Br Ginting; Suwarjo Suwarjo; Yakobus Ndona (Universitas PGRI Yogyakarta, 2026)
Peer support and mindfulness are external factors that are important for individuals, as social beings, to achieve high subjective well-being. This study aims to determine: (1) the effect of peer support on subjective well-being, (2) the effect of mindfulness on subjective well-being, and (3) the effect of peer support and mindfulness on the subjective well-being of secondary education students living in Yogyakarta dormitories. This study uses a quantitative approach with survey-type research. The data collection technique used a scale. The results showed that (1) peer support has a significant effect on subjective well-being, (2) mindfulness has a significant effect on subjective well-being, and (3) peer support and mindfulness have a significant effect on subjective well-being. This study aims to determine: (1) the effect of peer support on subjective well-being, (2) the effect of mindfulness on subjective well-being, and (3) the effect of peer support and mindfulness on the subjective well-being of students of secondary education living in the Yogyakarta dormitory. Keywords: mindfulness, peer support, subjective well-being